Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai Negeri Sipil Pada Dinas PPRDI Pekanbaru - Fadillah, Sonia Wati; Rofidah, Siti (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
This research aims to determine the influence of organizational culture on the performance of PPR Office. The type of research used in this research is quantitative. The population in this study were all PPR Office. The sample in this study amounted to 50 people. The data collection technique uses a questionnaire with a Likert scale, each of which has been tested and has met the validity and reliability requirements. The data analysis technique used in this research is simple linear regression. The results of the t test for the organizational culture variable have a positive and significant effect on the performance of PPR Office, because it has a significance value of 0.015 < 0.05 and a calculated t value of 3,882 > 2.010.